Peran Orang Tua dalam Mengembangkan Kecerdasan Emotional Dalam Perspektif Islam di Masa COVID-19 - Della Permatasari, Frisca (TADRIS: Jurnal Pendidikan Islam, 2021)
Emotional intelligence in children is very important for their growth and development. The role of parents is very supportive, especially during the COVID-19 pandemic. The role of parents is not only developing intellectual, but also emotional intelligence. The purpose of this study is to determine the role of parents in developing emotional intelligence in the perspective of Islam during the COVID-19 pandemic. The research method is triangulation (combination) of interviews, observations, and documentation. The results showed five parental roles, namely 1) supervising, 2) helping, 3) establishing communication, 4) giving responsibilities, 5) motivating children, and directing. The role of parents is still low at the supervision stage, where supervision by parents at this stage is difficult because children at this age are at the stage of exploration of the surrounding environment.